Application of novel security technique in cloud environment using attribute dependent authentication for health care - D. Deena Rose; C. Agees Kumar (Automatika, 2025)
Users of the cloud have been given access to high-quality, on-demand services, without being concerned about the sustaining infrastructure and software. While increasing the security concerns for private and confidential information, this brings emphasis back to the importance of trusting the use of the cloud for extremely sensitive data. In every facet of health, Cloud Health Information Systems (CHIS) become most important to patients and the healthcare sector. On the patient side, CHIS allows for the synchronization of clinical services, quick access to critical patient information, and the exchange of medical data and health records. A neural key sharing protocol has been developed, such that a violation of a shared secret key will prevent the disclosure of the real encryption key. To achieve better key security, the Strong key dependent Subkey Generation Algorithm (SKSGA) is proposed. A new Matrix based encryption algorithm (M-EA), is proposed in this research, for quick computational processing, effective and reliable data storage in the cloud. This research proposed a enhanced model for attainment of data privacy on the cloud, through the use of Attribute Dependent Multi Factor Authentication (ADMFA). In comparison to the current approaches, the suggested methodology demonstrated faster encryption and decryption times.